Assessing Future Teacher Leaders: An Analysis Of Leadership Skills in Pre-Service Teachers Using A Multi Domain Self-Assessment - Ainur Rosyid; Harlinda Syofyan; Tanzilla Rahma Azzahra (Proceeding of the International Conference on Global Education and Learning, 2024)
Teacher leadership is critical in shaping the educational environment and promoting positive change within schools. Teacher leadership fosters educational innovation and creates supportive learning environments. This study investigates the self-perceived leadership qualities of pre-service teachers, focusing on essential domains of teacher leadership, including self-awareness, leading change, communication, diversity, instructional proficiency, continuous improvement, and self-organization. Utilizing a structured survey instrument adopted and adapted from TLSA (Teacher Leadership Self-Assessment) by Katzenmeyer and Moller (2009). Data was gathered from a sample of teacher candidates to assess their competencies in these domains. The teacher candidates were the final-year Primary Teacher Education Program students at Esa Unggul University. The findings indicate varying levels of readiness among the participants. The categorical analysis provides insights into specific areas where future teachers demonstrate potential and highlights domains where further development may be beneficial. This research contributes to the understanding of teacher leadership in the context of teacher preparation programs and underscores the importance of targeted support in nurturing well-rounded teacher leaders. Implications for curriculum adjustments and the integration of leadership training in teacher education programs are discussed.